Synthesis and additive manufacturing of titanium carbide (Ti3C2Tx) MXene electrochemical sensors for nitrophenols - Robinson, Shiseido (Kansas State University, 2023)
The discovery of two-dimensional transition metal carbides and carbonitrides (MXene) has laid the foundation for further investigations in layered materials for its superior performance and applications. The material embodies countless desired properties such as hydrophilic surfaces, high electrical and thermal conductivities, large surface-to-volume ratio, excellent mechanical robustness, and efficient absorption of electromagnetic waves. The unique properties of these easily processable 2D layered MXene materials have been explored largely in energy storage devices and electromagnetic shielding applications for almost a decade. More recently, the material has attracted enormous interest in the field of chemical and biomolecule sensing owing to its varied chemical structure and ease of functionalization for sensitive and selective detection of various analytes. In this thesis, the large-scale exfoliation of the widely studied Ti₃C₂T[subscript x] MXene materials by adopting a minimally intensive layer delamination (MILD) etching route is demonstrated. Controlled chemical exfoliation conditions lead to the selective removal of the Al layer from Ti₃AlC₂ to form a few layered MXene. Subsequently, the exfoliated MXene clay was collected and re-dispersed in water and concentrated to form additive-free stable conductive inks. The ideal synthesis conditions for successful etching of MXene material were confirmed and examined through different structural and morphological characterizations such as X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and atomic force microscopy (AFM). Successfully synthesized MXene inks were used for dispense printing to fabricate sensor electrodes. The electrochemical performance of pure MXene and printed MXene electrodes were analyzed with a standard redox probe and its sensing behavior towards quantification of 4-Nitrophenol was examined.
Keywords: MXene; Sensors; Additive manufacturing; 2D materials; Electrochemistry